Comportamiento agronomico del híbrido de maíz (Zea mays L.) DK-7500 con cuatro distancias de siembra y tres niveles de fertilización en la zona de Quevedo - Guerra Briones, Roger Alexander (2015)
This research was carried out on the farm Selva Alegre, located in San Carlos, Canton Quevedo, Los Rios Province, at km. 1 Via San Carlos - Quevedo, to start the rainy season of 2015. The objective was to evaluate the agronomic performance of hybrid maize (Zea mays L.) DK-7500 with four-plant spacing and three levels of fertilization Quevedo area. A completely randomized design factorial 4 (planting distances) x 3 (levels of fertilization) with four replications was used. The variables evaluated were: plant height, height of insertion of ear, ear length, ear diameter, number of harvested ears per plot, number of diseased pods, number of rows per ear, weight of 100 grains, grain weight, weight of the cob, grain / cob ratio and yield (kg ha-1). The main results were: The planting distance D4 (0.85 mx 0.163 m) had the highest average diameter of the ear, number of ears per plot, grain weight and weight of the cob. With the level of fertilization F3 (EQ-02 16/12/25 = 280 kg ha-1, amides = 420 kg ha-1, potassium nitrate = 70 kg ha-1, magnesium sulfate = 70 kg ha-1) The greater plant height, diameter of the cob and row number per ear was obtained, the interaction D4 + F2 presented the largest diameter of the ear and number of ears per plot, while D4 + F3 reported the highest weight value grain. No differences (p> 0.05) in the performance of the hybrid DK-7500 planting distance, levels of fertilization and the interaction of these were found. The greatest benefit cost ratio was obtained from the interaction of D4 + F1 with a value of 0.91, indicating a return of 90.96%. Keywords: Hybrid corn, DEKALB-7500, Amides, Magnesium Sulfate, Potassium nitrate, agronomic performance.